The Role Of KnowledgeAbsorption In The Mediation Of The Effect Of Social Network On The Competitive Advantages Of “Batik”Micro Company - Poernomo, Djoko; Wahono, Puji; Puspitaningtyas, Zarah (Archives of Business Research, 2017)
"Batik" cloth is one of Indonesia’s pride product. When a micro company of batik fails to compete with similar products, then the pride is lost. Therefore, the existence of batik needs to be maintained. The purpose of the study explains the role of knowledge absorption in mediating the influence of social networks on entrepreneurship orientation, product innovation, and competitive advantage of micro company of batik. Research location in Regency of Banyuwangi, East Java Province, Indonesia. The study population is 154 craftsmen. Sampling technique using simple random sampling method. Number of respondents 111 micro company of batik or craftsmen. The data collection instrument used questionnaires. Data analysis using structural equation modeling with Smart PLS 3 software. The research findings show social network have a significant positive effect on the knowledge absorption, the knowledge absorption of mediates the significant positive effect of social network on entrepreneurship orientation and product innovation, positively significant to entrepreneurship orientation and product innovation but no significant positive effect on competitive advantage. While the influence of other research variables can be studied further on this scientific work.